2007
DOI: 10.1007/s11524-007-9193-3
|View full text |Cite
|
Sign up to set email alerts
|

Deprivation Indices, Population Health and Geography: An Evaluation of the Spatial Effectiveness of Indices at Multiple Scales

Abstract: Area-based deprivation indices (ABDIs) have become a common tool with which to investigate the patterns and magnitude of socioeconomic inequalities in health. ABDIs are also used as a proxy for individual socioeconomic status. Despite their widespread use, comparably less attention has been focused on their geographic variability and practical concerns surrounding the Modifiable Area Unit Problem (MAUP) than on the individual attributes that make up the indices. Although scale is increasingly recognized as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
149
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(163 citation statements)
references
References 41 publications
3
149
1
10
Order By: Relevance
“…However, there are also other factors, such as care-seeking behaviors, socioeconomic status, and population density, which determine which subpopulations are at higher risk for disease (17). Many of these factors also have a geographic expression; theoretical and empirical evidence from public health, geography, and sociology indicate that people with similar characteristics cluster in space, creating larger spatial patterns within a population (18,19). Thus, spatial analysis of PCV trial data in other regions may similarly provide insight to which populations should be targeted Note: Numbers in the three estimate columns are the SARAR model regression coefficients for each endpoint; numbers in the SE columns are the corresponding SEs for the regression coefficients; exact P values are also provided for each estimate.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are also other factors, such as care-seeking behaviors, socioeconomic status, and population density, which determine which subpopulations are at higher risk for disease (17). Many of these factors also have a geographic expression; theoretical and empirical evidence from public health, geography, and sociology indicate that people with similar characteristics cluster in space, creating larger spatial patterns within a population (18,19). Thus, spatial analysis of PCV trial data in other regions may similarly provide insight to which populations should be targeted Note: Numbers in the three estimate columns are the SARAR model regression coefficients for each endpoint; numbers in the SE columns are the corresponding SEs for the regression coefficients; exact P values are also provided for each estimate.…”
Section: Discussionmentioning
confidence: 99%
“…Obvious differences of population between census tracts and census blocks exist when analyzing a social index. Schuurman et al (2007) found significant differences in populations classified by deprivation in census blocks and census tracts. We therefore claim that some health-related processes and relationships may be similar at different scales and contexts, but all oversimplification in the interpretation of statistical results should be avoided, and the MAUP and the UGCoP always need to be monitored to ensure the best possible decision making.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the important role that the area-based measures of deprivation and healthcare accessibility play for health policy making, little attention has been paid to evaluating the contextual and scale implications of these measures, and only few studies have addressed this issue (Cabrera-Barona et al 2016b;Dumedah et al 2008;Haynes and Gale 2000;Schuurman et al 2007;Wei et al 2017). The phenomenon of the modifiable areal unit problem (MAUP) usually causes the results of statistical analyses to differ according to the scale and size of the spatial reporting units (Briant et al 2010;Openshaw 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have either not explored factors associated with resilience (Tunstall et al, 2007) or have used area units with large populations (Doran et al, 2006;Mitchell et al, 2009;Tunstall et al, 2007). Researchers argue that the modifiable area unit effect is best ameliorated by using a small unit of analysis (Shuurman, Bell, Dunn, & Oliver, 2007). Conversely, the sparsely populated rural areas and relatively small population of New Zealand can be a concern when using rates due to small denominators leading to spurious high proportions and the potential lack of representativeness .…”
Section: Discussionmentioning
confidence: 99%